Penerapan Akupresur dalam Mengurangi Mual Muntah pada Pasien Kanker dengan Kemoterapi - Ni Nyoman Budi Indrayanti; Allenidekania Allenidekania; Dewi Gayatri (Journal of Telenursing (JOTING), 2022)
This study aims to analyze the use of acupressure in reducing chemotherapy-induced nausea and vomiting. The method used is a systematic review through the Proquest database, ScienceDirect and Scopus. The results showed that of the eight articles reviewed, six reports showed that acupressure effectively reduced nausea and vomiting in patients receiving chemotherapy and two articles stated that there was no significant difference between the acupressure intervention group and the control group. In conclusion, acupressure can reduce chemotherapy-induced nausea and vomiting. Keywords: Acupressure, Chemotherapy, Nausea Vomiting, Cancer Patients